PENINGKATAN HASIL BELAJAR SISWA KELAS XI TSP SMK NEGERI 3 MATARAM PADA PELAJARAN PENDIDIKAN KEWARGANEGARAAN DENGAN METODE KOOPERATIF TIPE STAD TAHUN PELAJARAN 2014 -2015 - Ni Made Suprapti Nurmala Dewi (Valid: Jurnal Ilmiah, 2016)
The aims of this research is to know how the cooperative method ( STAD) or students’ team achievement can improve the students’ result in Teaching learning processes in civilization lesson. The research used 2 cycles. The cycles consisted of 4 (four) steps. They were planning, acting, observation and reflexing. The conclusion of the research are, 1) the research shows that the students’ knowledge can increase. 2) From observation data, it shows that the students who has high ability are more active and enthusiasts so the class look so life in the process, they can take and give each other in finishing their assignment. 3) The average result of the learning process shows that in the first cycle 62.19 and in the second cycle is 78,28. It shows that the class action research of civilization lesson is success because the students’ result of XI TSP is increase of the at SMKN 3 Mataram in 2014/2015 academic year